Driver Behavior Monitoring and Alerting System Using Samrt Phone - Kanimozhi, J; Subramanian, R (International Journal of Computer Sciences and Engineering, 2025)
Objective of this research work is to build a driver monitoring system. Nowadays because of the road accidents death rate is keep on increasing and the vehicle production rate is also increasing which leads to pollution. Driver Alert application is developed to alert the drivers for dangerous driving events with respect to driver behavior and road conditions. This system focuses on the most commonly occurring dangerous driving events: drowsy driving, inattentive driving, lane weaving and drifting, and vehicle detection. Driver behavior is monitored with his head pose and eye state using front camera of the mobile. Similarly, in the rear camera the dangerous driving conditions at the road are detected with respect to lane conditions and vehicles (living being, non-living being) on the road. If the system detects any dangerous events on any of the camera, then it alerts the driver by displaying an alert icon on the mobile’s touch screen along with an audible alert message. To process the video frames from both front and rear camera a context-switching algorithm is used. So that the driver will be notices in both the way and alerted for them. An Emergency system is developed to tell about the driver problem to the outside people for dangerous events like accident, heart attack or any health issue which makes him distracted while driving.